Training to Lead in an Era of Change: Insights From Ad Agency Leaders. (May 2020) - Habib, Sabrina; Patwardhan, Padmini
This study examines leadership training in advertising. Interviews with U.S.-based agency professionals revealed the lack of a systematic approach to leadership development. There was a consensus among professionals that training (whether formal or informal) is needed. Despite need and benefits of establishing leadership training programs in agencies, participants acknowledged barriers to doing so. The study also finds a role for advertising education to train the next generation of advertising leaders.